2021
DOI: 10.3389/fsurg.2021.773653
|View full text |Cite
|
Sign up to set email alerts
|

Fast-Track in Minimally Invasive Gynecology: A Randomized Trial Comparing Costs and Clinical Outcomes

Abstract: Study Objective: Evaluate the effects of a fast-track (FT) protocol on costs and post-operative recovery.Methods: One hundred and seventy women undergoing total laparoscopic hysterectomy for a benign indication were randomized in a FT protocol or a usual care protocol. A FT protocol included the combination of minimally invasive surgery, analgesia optimization, early oral refeeding and rapid mobilization of patients was compared to a usual care protocol. Primary outcome was costs. Secondary outcomes were lengt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…[11][12][13] abdominal hysterectomy (AH Emery et al observed a significant (by 20%) reduction in hospitalization time for FTS compared to usual care surgery for benign laparoscopic hysterectomy. 14 Studies by Meyer et al and Yoong et al also showed that FTS was associated with a decreased LOS in cancer patients who underwent gynecologic laparotomy and vaginal hysterectomy, respectively. 15,16 This observed difference in LOS may be explained by the primary objective of FTS as a multimodal approach to patient care: to prevent or minimize factors that can negatively affect patient recovery throughout the entire perioperative period, such as discomfort levels, stress and anxiety, inadequate pain management, * p-value statistically significant, $ Wilcoxon rank sum test with continuity correction was used to assess the difference in operative characteristics and postoperative degree of pain, # Fisher's exact test was used to assess the difference in frequency of postoperative complications between groups, VAS: visual analog scale; LOS: length of stay.…”
Section: Discussionmentioning
confidence: 93%
“…[11][12][13] abdominal hysterectomy (AH Emery et al observed a significant (by 20%) reduction in hospitalization time for FTS compared to usual care surgery for benign laparoscopic hysterectomy. 14 Studies by Meyer et al and Yoong et al also showed that FTS was associated with a decreased LOS in cancer patients who underwent gynecologic laparotomy and vaginal hysterectomy, respectively. 15,16 This observed difference in LOS may be explained by the primary objective of FTS as a multimodal approach to patient care: to prevent or minimize factors that can negatively affect patient recovery throughout the entire perioperative period, such as discomfort levels, stress and anxiety, inadequate pain management, * p-value statistically significant, $ Wilcoxon rank sum test with continuity correction was used to assess the difference in operative characteristics and postoperative degree of pain, # Fisher's exact test was used to assess the difference in frequency of postoperative complications between groups, VAS: visual analog scale; LOS: length of stay.…”
Section: Discussionmentioning
confidence: 93%
“…The ability to extirpate the non-descent uteri vaginally is the hallmark of the real gynecologic surgeon (11,22,64). TVH is the gold stranded for benign uterine condition for uterine size up to 12 weeks or up to 280 grams according to ACOG, SOGC, ISGE, RCOG, AAGL, DHA, SGS (4,5,8,9,10,13,66) as TVH is the most costeffective, value-based over TAH, TLH (7,34,36,37,39,42,47,48,58,59,60,61,62,64,67,68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ability to extirpate the non-descent uteri vaginally is the hallmark of the real gynecologic surgeon (11,22,64). TVH is the gold stranded for benign uterine condition for uterine size up to 12 weeks or up to 280 grams according to ACOG, SOGC, ISGE, RCOG, AAGL, DHA, SGS (4,5,8,9,10,13,66) as TVH is the most costeffective, value-based over TAH, TLH (7,34,36,37,39,42,47,48,58,59,60,61,62,64,67,68 ). A pioneer in gynecologic surgery takes multiple steps in TVH beyond this edge and tried all cited contraindications with excellent success as prior pelvic surgeries include cesarean sections, larger uteri up to 3 kilograms, nulliparity, absent prior vaginal birth, morbid obesity, need for oophorectomy (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)63,66).…”
Section: Discussionmentioning
confidence: 99%